Which fiscal union for the euro area? - Agnès Bénassy-Quéré; Xavier Ragot; Guntram B. Wolff (Bruegel, 2016)
[Highlights] Fully-fledged federations assign fiscal policy stabilisation largely to the federal level, based on a relatively large budget. In the euro area, a large federal budget is unrealistic at the current level of political and societal integration, and fiscal stabilisation will continue to rely mainly on national policies. For aggregate fiscal policy to become more stabilising with respect to the economic cycle, while achieving long-term sustainability, it is necessary (i) to avoid imposing self-defeating fiscal adjustments on crisis countries by making sovereign debt restructuring a real possibility (which involves strengthening the banking sector and extending the remit of the European Stability Mechanism); (ii) to task the planned independent European Fiscal Board with delineating exceptional times during which fiscal coordination is needed on top of monetary policy; (iii) to make national fiscal policies more stabilising by allowing incremental investment and unemployment spending to be shifted from bad to good times based on national adjustment accounts. We also recommend a move towards a European unemployment (re-)insurance scheme targeted at `large' shocks, with varying contributions from countries and a minimum set of labour-market harmonisation criteria, which in any case are desirable for the functioning of monetary union.
Keywords: 330